Asymmetric Hydroamination: A Survey of the Most Recent Developments. Issue 16 (1st March 2013) - Hannedouche, Jérôme; Schulz, Emmanuelle
Abstract Asymmetric hydroamination allows the direct and selective formation of a new CN bond as a simple procedure towards valuable scalemic synthons. Huge efforts have recently been made to overcome the challenges associated with this transformation. This non‐comprehensive Concept article aims at pointing out the most recent and original progresses, offering nearby developments, and addressing the next challenges.